Effects of Geomagnetic Disturbances on Human Health and Cardiovascular Diseases - Shamyar, S.
Geomagnetic disturbances (GMD) are significant perturbations in Earth's magnetosphere caused by solar wind interactions. This paper explores the impact of GMD on human health, particularly cardiovascular diseases (CVD). The proposed mechanisms include alterations in the autonomic nervous system, circadian rhythm disturbances, changes in blood viscosity, and psychiatric effects. Understanding these impacts can enhance medical protocols and patient care during geomagnetic storms.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture